Kendali Tegangan Output Buck Converter Berbasis Fuzzy Mamdani - Ulandari, Putri; Yuhendri, Muldi (Jurnal Teknik Elektro Indonesia, 2024)
The source of energy used in everyday equipment is electrical energy. Starting from a small scale from household needs to a large scale as an energy source for industry, there are two types of voltage commonly used for various purposes, namely alternating voltage or also known as alternating current (AC) and direct voltage or direct current (DC). To get a DC voltage that is in accordance with the voltage standards required by the equipment, a voltage source is needed that can produce a voltage that varies the equipment is to use a converter then the output voltage needs to be controlled. Controlling the output voltage at the buck converter using the Mamdani fuzzy method. This control system is designed and implemented on the Arduino Mega 2560 platform which is programmed using Simulink Matlab. Mamdani fuzzy method is used to determine the duty cycle based on the rules in the rule base, which consists of five membership functions. The proposed system is tested and verified through experiments with an input voltage of 24 Volts and an output voltage varying from 6, 9 Volts to a maximum of 12 Volts. The experimental results show that the buck converter output voltage control system using Mamdani fuzzy successfully controls the buck converter output voltage according to the specified reference value. This can be seen from the resulting output voltage error, with a maximum of only 2 % when the reference voltage is at 12 Volts.